The Influence of Vocational Education Transformation Direction and Learning Strategy Towards Vocational Student’s Employability in Malaysia - Ghazali @ Hassan Sulaiman; Abdul Said Ambotang (2018)
This study aims to identify the influence of the transformation of vocational education and learning strategies on the employability of Vocational Basic Education (VBE) pupils in selected daily high schools in Malaysia as a preparation of VBE students to pursue studies at technical or vocational institutions of higher learning institutions or institutions of higher learning to provide students to enter the realm of work. In addition, the objective of this study was to identify the level of direction of the transformation of vocational education, the level of learning strategies and the level of employability among VBE students, identify the differences in employability among VBE pupils based on demographics, identify the relationship between the direction of the transformation of vocational education and learning strategies with VBE students' employability and identifying the influence of the forecasting factor, the direction of the transformation of vocational education and the learning strategy towards the employability of VBE students. The findings show that the direction of the transformation of vocational education especially the construct of the vocational element is high while the level of learning strategies and the level of employability among VBE students is moderately high. There is a significant difference in VBE students' employability on the basis of gender while the course does not have significant differences. In terms of the relationship between the variables, there is a significant correlation between the direction of the transformation of vocational education and the learning strategy with the employability of the VBE student to work while the factor of the predictor of the study found that there was a significant influence of the forecasting factor in the direction of the transformation of vocational education and learning strategies on the employability of VBE students. The implication of this study suggests that emphasis on employability needs to be constantly improved and the opportunity of VBE pupils to pursue higher education at higher educational institutions or institutions, especially in technical and vocational fields, should be expanded so that VBE pupils' employability will become more prominent during the career market.